(untitled) (Vietnam Journal of Community Medicine, 2022)
A cross-sectional study was conducted on 200 staff working at Kien Giang Center for Disease Control and Prevention from 01/2021 to 06/2021 to assess their satisfaction with their job and identify some associated factors. Results of the study showed that all of the percentages of satisfaction of staff with different aspects of their job were high (>75%). The percentage of satisfaction with of co-worker relationships was the highest (86 %) and the percentage of satisfaction with the management mechanism was the lowest (75.5%). The percentage of staff’s overall satisfaction (satisfaction with all factors) was 76.5%. Some associated factors with staff’s satisfaction were sex, seniority and type of work (p<0,05).